2007
DOI: 10.1007/s00384-007-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of familial colorectal cancer with variants in the E-cadherin (CDH1) and cyclin D1 (CCND1) genes

Abstract: We report a potential association of variants in the CCND1 and CDH1 genes with fCRC using a unique study design with phenotypic extremes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…To formally evaluate dosage effect within different categories, we applied the Cochran-Armitage tests for trend before and after removing the outlier studies (Table 2A and B). Significant dosage effects were observed in overall (P = 0.00001) and Asians (P = 0.00001); however, trend was not significant in Caucasians after removing the heterogeneous studies (20,22,26,38,41,57). Among the cancer types, significant dosage effects were observed in blood-related (P = 0.0001), genitourinary (P = 0.0001), and other cancers (P = 0.001; Table 2A) before excluding the outliers and none were significant after outlier removal (Table 2B).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To formally evaluate dosage effect within different categories, we applied the Cochran-Armitage tests for trend before and after removing the outlier studies (Table 2A and B). Significant dosage effects were observed in overall (P = 0.00001) and Asians (P = 0.00001); however, trend was not significant in Caucasians after removing the heterogeneous studies (20,22,26,38,41,57). Among the cancer types, significant dosage effects were observed in blood-related (P = 0.0001), genitourinary (P = 0.0001), and other cancers (P = 0.001; Table 2A) before excluding the outliers and none were significant after outlier removal (Table 2B).…”
Section: Resultsmentioning
confidence: 97%
“…1). To identify which of the 60 studies that may be sources of heterogeneity, we used the Galbraith plot and accordingly identified 12 studies (20,22,23,26,37,38,41,43,44,46,57,62) as the main contributors (Table 1; Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results by gender were not provided in the publications; thus, separate meta-analyses on men and women were not possible. However, for ff and CRC, the only study including a higher proportion of women than men (52) showed a statistically significant positive association (RR ¼ 1.84, 1.15-2.94), whereas studies including a higher proportion of men than women (19,50,53) or an equal proportion of men/women (21,51,(54)(55)(56)(57) (Table I). From these, 4 studies also reported on BsmI (19,20,51,54) and 4 on Fok I (19,51,54,57).…”
Section: Vdr Polymorphismsmentioning
confidence: 98%
“…6 With respect to colorectal cancer in particular, subjects with hereditary nonpolyposis colorectal cancer who carry the rs9344 polymorphism have been reported to acquire the disease at an earlier age. [7][8][9] Also, carriers of the A allele appear to be more frequent among individuals who developed non-syndromic colorectal cancer before the age of 60, 10 subjects with familial colorectal cancer 11,12 and affected women. 13,14 Other reports, however, do not subscribe to rs9344 genotype being a modifier of the colorectal cancer phenotype.…”
Section: Introductionmentioning
confidence: 99%